CONSTITUTIONAL CONTROL IN PERU: A MODEL STILL TO ARM? - López Flores, Luciano (2017)
This paper deals with the model of constitutional control in Peru. The author comes to historical, conceptual and jurisprudential sources for, on the one hand, identify and understand the context that gives rise to its origin and secondly, to analyze its procedural operation in Peru, baring the deficiencies that presents. Hence it is claimed that the Peruvian judicial review is a “model even put together”. Finally, it states that the exploration of judicial review serves to clarify some concepts that link it very closely with constitutional interpretation, in the light not only of what holds the current comparison doctrine but also its reception in the jurisprudence of the Peruvian Constitutional Court.